A Discussion on A Code Sound Reading System: A Case Study of I Can Read Greenville Language Center - Wiwik Andreani; Junita Junita (Bina Nusantara University, 2014)
Article described the code sound reading system applied in I Can Read (ICR) Greenville language center. The research was done qualitatively through the observation of teaching and learning process in three different classes of ICR 1 level at the center. A pre-test and post-test for reading were taken from Book 2 of ICR 1. Participants were three classes with three different teachers having different working experiences. The results of the research were: (1) the use of code sounds in reading was useful to improve students’ reading skill which was shown by the increasing of correctly pronounced code sounds; (2) the students’ reading skill and reading comprehension had improved, regardless the teachers’ teaching style. In conclusion, a code sound reading system is successful in helping students to improve their reading skill and reading comprehension, regardless the teachers’ teaching style.